Design and Optimization of the Heatsink of a Level 1 Electric Vehicle Charger - Iheanyi Emmanuel Ebere; Ashraf Ali Khan; Samuel Ogundahunsi; Emeka Ugwuemeaju; Usman Ali Khan; Shehab Ahmed (Energies)
The onboard circuits of EV chargers comprise heat-producing electronic devices such as MOSFETs and diodes for switching and power conversion operations. A heatsink must dissipate this generated heat to extend the devices’ life and prevent component thermal stress or failure. This study primarily investigates the optimal heatsink geometry and pin configuration, which offers the most efficient temperature versus cost performance. MATLAB/Simulink (R2024a) was used to model a Level 1 charger using eight MOSFETs and four diodes. Various heatsink geometries were modeled using the ANSYS (2024 R1) Workbench and Fluent software to optimize the sink’s thermal performance. The analyses were performed under transient conditions using natural and forced cooling scenarios. The 2 mm wide plate fin heatsink with 44 fins yielded the best result. Further enhancement of the best-performing naturally cooled model improved the switches and diodes temperatures by 14% and 4%, respectively. The performance of the heatsink was further improved by applying a cooling fan to achieve an up to 25% diode and 40% MOSFET thermal dissipation efficiency. The results of this study show that the most efficient cooling performance and cost are realized when the optimum combination of fin spacing, proximity from the cooling fan, and fin geometry is selected.